Akuntansi Syariah Sebagai Sumber Informasi Bagi Perusahaan Yang Patuh Terhadap Syariah - Liza Ulfitri; Rayyan Firdaus (STIKes Ibnu Sina Ajibarang, 2024)
Islamic accounting is a system grounded in Islamic sharia principles, such as fairness, transparency, and social responsibility. This accounting framework is designed to help companies ensure that their operations and financial reports comply with sharia law. This article examines the role of Islamic accounting as a source of information for sharia-compliant companies. Islamic accounting offers a financial reporting framework that reflects adherence to Islamic values, including the prohibition of usury, gharar (excessive uncertainty), and haram (forbidden) transactions. By providing accurate and relevant information, Islamic accounting aids companies in making strategic decisions aligned with sharia principles. Additionally, it assures stakeholders, including investors and the public, that the company’s operations are conducted ethically and responsibly. Therefore, Islamic accounting functions not only as a financial reporting tool but also as a strategic framework for managing companies committed to sharia compliance.